Identification of pellicle formation related microorganisms in traditional Sichuan paocai through metagenomic sequence and the effects of Baijiu/Salt on pellicle and volatile components. (September 2022) - Xian, Shuang; Zhong, Hengyan; Yi, Bai; Liu, Xingyan; Shen, Guanghui; Li, Meiliang; Zhang, Zhiqing; Luo, Qingying; Li, Shanshan; Zhou, Man; Xu, Fei; Chen, Anjun
Highlights: The pellicle-forming related microbes in traditional home-made Chinese paocai were first identified through metagenomic sequencing. The pellicle formation related microorganisms mainly belonged to six genus, including Kazachstani a, Lactobacillus, Pichia, Candida, Lachancea and Saccharomyces . Baijiu was effective to restrain the pellicle and improve the flavor of paocai. Abstract: The occurrence of pellicle on the surface of paocai brine is a common undesirable phenomenon during the multi-rounds of paocai fermentation, which is mainly caused by the growth of microorganisms related to pellicle formation. But the detailed information on these microorganisms and volatile components produced by them, as well as the changes of the microorganisms during the process of paocai recovery, are still rare in the literature. Therefore, the purpose of this study was (1) to analyze the pellicle formation related microorganisms by comparing the differential microorganisms in initial brine and the brine when pellicle occurred through metagenomic sequencing technology, (2) to explore the changes of microorganisms in the fermentation system after addition Baijiu and/or salt, and (3) to further detect the VOCs in paocai samples by gas chromatography-mass spectrometry (GC–MS). The relationship between VOCs and the selected marker microorganisms was also determined. The results showed that the diversity of fungi was increased when pellicle formed, the pellicle formation related microorganisms mainly belonged to six genus, including Kazachstani a, Lactobacillus, Pichia, Candida, Lachancea, and Saccharomyces . Apart from the unknown function and basic life activities of microorganisms, the metabolic activities of these pellicle formation related microorganisms were mainly carbohydrate transport and metabolism, and amino acid transport and metabolism. The growth of pellicle formation related microorganisms could be inhibited by adding Baijiu (1.5% v/v), but the addition of salt (7% salt (w/v) did not promote this inhibitory effect. Through PCA analysis, it was found that the VOCs of paocai were significantly affected by adding Baijiu and Baijiu and salt. The undesirable smell at the beginning of pellicle formation may be related to Propanoic acid, hexyl ester, 1, 3-Dimethyl-1-cyclohexene, Oxime-, methoxy-phenyl- and Phenylethyl Alcohol.